Structure Phenomenology Preconscious Formation in the Epistemic Disclosure of Reality - Witzenmann, Herbert (Bloomsbury Academic, 2022)
This is the first English translation of Herbert Witzenmann's seminal work,Strukturphänomenologie, which departs from the traditional phenomenological methods of Husserl, Sartre, and Merleau-Ponty to introduce a fresh approach to the nexus of consciousness and reality. In Structure Phenomenology, published open access, Witzenmann argues for the active mental, yet mostly pre-reflective, participation of humans in the emergence of individual consciousness of all kinds and the basic structure that determines it. While Witzenmann ascribes a derivative or memorative status to habitual states of phenomenal consciousness, even if they seem to refer to present objectivity, he proposes that the underlying formative processes be unveiled and explored through systematic first-person observation. Through his logically grounded and experience-based approach, he contends that it is not neural processes that produce consciousness, but rather one's own preconscious rootedness in reality which can be made conscious. Influenced by the writings of Rudolf Steiner and Johann Wolfgang von Goethe, Witzenmann's innovative approach casts new light on a number of philosophical, psychological, and scientific issues: from being and becoming to temporality and presence, and from remembering to mind and body. Even freedom takes on a new meaning when reality is not pre-given to human consciousness, but is rather a result of human participation in the basic process. This annotated translation makes Witzenmann's text accessible to an English audience for the first time and, with a comprehensive editorial introduction by Johannes Wagemann, situates his ground-breaking insights within the development of phenomenology, as well as in current philosophical and psychological debates. The ebook editions of this book are available open access under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com.